Remarkable degradation of methyl orange by tetragonal zirconia catalyst - Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier Ltd., 2018)
A t-ZrO2 catalyst was prepared through a simple electrochemical method at a lower calcination temperature which resulted in superior photoactivity toward methyl orange (MO) decolorization. An amount of 0.4 g Lâ1 of t-ZrO2 catalyst was found to be an optimum dosage for 10 mg Lâ1 MO, which resulted in a complete decolorization after 1 h of contact time at pH 3 under fluorescent light. Good photo-activity toward decolorization of MO promises the t-ZrO2 catalyst to be used in textiles industry wastewater treatment and also other applications